The cytokine response to mucosally transmitted feline immunodeficiency virus infection - Avery, Paul R., author; Hoover, Edward A., advisor; Wilcox, Christine, committee member; Smith, Joseph, committee member; Titus, Richard G., committee member (Colorado State University. Libraries, 2002)
Understanding the immune response to retroviral infections is critical to the rational design of prevention and intervention strategies. The studies reported herein were designed to help understand the interaction of feline immunodeficiency virus (FIV) and the initial host immune response. In addition, we have begun to explore the use of adenoviral-mediated expression of murine interleukin 12 (mIL12) as a means to shift the immune response to favor host control of FIV. We were able to document a significant increase in the T lymphocyte production of interleukin 10 (IL10) in both the spleen and colic lymph nodes of infected cats at four weeks post rectal infection (PI). At ten weeks PI, the high levels of IL10 were maintained yet the level of IFNγ in CD8+ T cells had increased to an even greater extent thereby normalizing the T cell IFNγ:IL10 ratio. The normalization of this ratio corresponded with a significant reduction in viral RNA levels in both the spleen and the colic lymph node T cells. Macrophage production of interleukin 6 (IL6) was increased by 10 weeks PI and this was correlated with the rising macrophage viral RNA levels noted at this timepoint. To explore the significance of the early rise in interlukin 10, we utilized murine IL12 as a means to preferentially induce a strong cell-mediated immune response. Recombinant mIL12 augmented mitogen-induced proliferation of feline PBMC and induced the production of feline IFNγ in vitro. Cats treated with varying doses of mIL12 intraperitoneally developed dose-related hematotoxicities typical of those seen in mice. A replication defective adenoviral vector expressing mIL12 was shown to productively infect feline cells and produce biologically active mIL12. Intraperitoneal adenovirus-mediated mIL12 delivery resulted in the systemic induction of feline IFNγ and, in a preliminary experiment, appears to have delayed the rise in plasma FIV RNA levels in mucosally infected cats. Future experiments are planned to expand upon these findings and to further define the significance of the early IL10-dominated cytokine response to FIV infection.
Keywords: pathology; immunology; molecular biology